Tata Kelola Labortorium Untuk Meningkatkan Manajemen Pendidikan Sains di Lembaga Pendidikan Islam (MA As-Sa’adah Sumedang) - Irawan Irawan; Ishma Shafiyatu Sa’diyah; Tedi Priatna (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Science governance in institutions is a plan or a pattern that is used as a guide in planning learning in the laboratory or learning in tutorials and for determining learning tools including laboratory equipment, books, curriculam, and etc. The laboratory is a place for security, experiments, training and testing of knowledge and technology concepts. Science laboratory management includes planning, organizing, regulating, recording, maintenance, and funding. The function of the science laboratory at the institution is to improve the quality of student learning depending on the views of the teacher concerned about science and learning (learning). The purpose of this study was to analyze the management description of the availability of equipment, teaching materials, availability of administration and implementation of practicum activities in the As-Sa'adah Sumedang MA Science laboratory. This study uses a qualitative method. The techniques used in data collection were observation, interviews, and documentation studies. The results of research at the As-Sa'adah MA Science Laboratory showed that the availability of practicum equipment was found to be in the poor category, the availability of teaching materials was to be in the poor category, the availability of administration laboratory obtained the average is in the less category and the implementation of practicum activities obtained the average is also in the less category. The results of this study can be used as a consideration for the head of the laboratory to improve Management Educational sciencs implementation in schools. Keywords: Management Educational sciencs ; Activities; Administration; Materials